The Effectiveness of the @Cerita_Asahan Instagram Account as a News Aggregator to Fulfill the Information Needs of Followers - Farhan, Muhammad; Bahri, Andini Nur (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
The effectiveness of Instagram accounts and the information conveyed to the internet community have a close relationship. Effectiveness is the expected impact, and then it can be assessed from the results of success or achievement of previously planned goals. The @cerita_asahan Instagram account acts as a news aggregator because it collects news from primary sources and delivers important information to the internet community quickly so that its effectiveness can be measured in terms of meeting the information needs of their followers. So the purpose of this study is to measure the effectiveness of the @cerita_asahan account in meeting the information needs of its followers. The study population was the followers of the account, with 100 people sampled. Using quantitative methods, the results showed the effectiveness of the @cerita_asahan account as a news aggregator in fulfilling followers' information needs with a simple linear regression coefficient and partial t-test, which resulted in a partial correlation of 0.846, in accordance with the high category according to Cohen's d interpretation criteria. The t-count value of 11.475 is greater than the t-table of 1.987, indicating that the null hypothesis is rejected and the alternative hypothesis is accepted, which means that there is a significant and positive effectiveness between the @cerita_asahan account and the fulfillment of the information needs of its followers. Therefore, it is concluded that the @cerita_asahan Instagram account is very effective in meeting the information needs of its followers, so this research is expected to be a good suggestion for the development of the @cerita_asahan Instagram account.